‘A heart within, a God overhead’: the making of nuclear medicine in postcolonial India, 1947–1985 - Kapil Patil (Medical History, 2026)
Abstract The onset of the atomic age in India embodied a unique postcolonial ambition to harness atomic energy for peaceful purposes. Within this vision, nuclear medicine became a key instrument to modernise the country’s colonial healthcare infrastructure. For India’s nascent community of radiologists, radioisotopes offered a promising frontier in clinical research and therapeutic applications. Yet the development of nuclear medicine was far from a straightforward extension of atomic research into clinical practice. Instead, it took shape within a centralised framework that concentrated technological resources and expertise in a small number of metropolitan centres. The centralisation of nuclear medicine practice was not merely a response to the resource constraints of a postcolonial economy. It also reflected a technopolitical project that linked the modernisation of public healthcare to expanding atomic energy infrastructure. Situating the emergence of nuclear medicine within the intertwined histories of radiology, cancer care, and atomic energy research, the paper examines the postcolonial aspiration to harness advanced medical specialities through the atomic enterprise. In doing so, it unpacks the technopolitics of nuclear medicine, highlighting the politico-epistemic negotiations that shaped its institutionalisation in India.